2013
DOI: 10.1093/mnras/stt881
|View full text |Cite
|
Sign up to set email alerts
|

Simulated observations of young gravitationally unstable protoplanetary discs

Abstract: The formation and earliest stages of protoplanetary discs remain poorly constrained by observations. ALMA will soon revolutionise this field. Therefore, it is important to provide predictions which will be valuable for the interpretation of future high sensitivity and high angular resolution observations. Here we present simulated ALMA observations based on radiative transfer modelling of a relatively massive (0.39 M ⊙ ) self-gravitating disc embedded in a 10 M ⊙ dense core, with structure similar to the pre-s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 48 publications
2
33
2
Order By: Relevance
“…However, in the latter work, inclination was affecting the simulated ALMA maps when a high-order, tightly wound spiral pattern was present. In our case, the disk, being very massive, develops only global, large-scale, large pitch angle m = 2-4 modes (see also Dong et al 2015), whose morphology is inherently less affected by inclination, as was also found by Douglas et al (2013). Our simulations have some limitations that could have an impact on the ALMA mocks.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…However, in the latter work, inclination was affecting the simulated ALMA maps when a high-order, tightly wound spiral pattern was present. In our case, the disk, being very massive, develops only global, large-scale, large pitch angle m = 2-4 modes (see also Dong et al 2015), whose morphology is inherently less affected by inclination, as was also found by Douglas et al (2013). Our simulations have some limitations that could have an impact on the ALMA mocks.…”
Section: Discussionmentioning
confidence: 61%
“…Since accretion is filamentary and patchy in a turbulent core (e.g., Hayfield et al 2011) inhomogeneities in density and temperature might arise in the outer disk that could render clump identification more difficult. However, using mocks for both continuum and molecular line emission/absorption, Douglas et al (2013) have shown that a strong spiral pattern should be detectable with ALMA even in embedded disks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In both cases, the dominant motion of the compact flattened structure during the embedded phase is infall rather than rotation. There are indeed sources where higher sensitivity and spatial resolution observations such as with Atacama Large Millimeter/submillimeter Array (ALMA) can detect features associated with disk instabilities (e.g., Cossins et al 2010;Forgan et al 2012;Douglas et al 2013). …”
Section: Disk Stabilitymentioning
confidence: 99%